Matematyka
neetia1
2017-06-22 15:55:44
rozłóż wielomiany na czynniki dzięki z góry
Odpowiedź
03kasia4
2017-06-22 20:52:26

[latex]a)\W(x) = x^{3}-2x^{2}-3x = x^{3}+x^{2}-3x^{2}-3x=x^{2}(x+1)-3x(x+1)=\\(x+1)(x^{2}-3x)=(x+1)cdot x(x-3)=x(x+1)(x-3)[/latex] [latex]b)\W(x) = (-x^{3}+4x^{2}-3x)(x^{2}+5x+4)=\\=-x(x^{2}-4x+3)(x^{2}+5x+4)=\\-x(x^{2}-3x-x+3)(x^{2}+x+4x+4)=\\=-x[x(x-3)-(x-3)]cdot[x(x+1)+4(x+1)]=\\=-x(x-3)(x-1)(x+1)(x+4)[/latex] [latex]c)\W(x) = 9x^{3}-4x^{2}-27x+12=x^{2}(9x-4)-3(9x-4)=\\=(9x-4)(x^{2}-3) = (9x-4)(x+sqrt{3})(x-sqrt{3})[/latex]

Dodaj swoją odpowiedź